Is mobile phone a source of hand discomfort for university students? - Fouzia Batool; Anum Khan; Khusbakht Bibi; Ubaid Ullah; Hania Farheen (Journal Riphah College of Rehabilitation Sciences, 2019)
Background: Mobile phones users are increasing with the technology advancement and it became one of the important assets of youngster’s life. Every device is having its positive as well as negative effects. Due to more usage of these mobile phones, people are complaining of some musculoskeletal and neurological discomforts.